PANDANGAN MASYARAKAT UMUM TERHADAP NILAI MORAL UPACARA SEBA BADUY - Muhammad Rafik; Maftuh Basyuni; Enggar Utari; Ika Rifqiawati (Jurnal Budaya Nusantara, 2023)
The seba ceremony is a religious ritual activity carried out by the Baduy tribe, Kanakes Village, Lebak Regency. This activity has been carried out for centuries since the Banten sultanate was established and has become the public spotlight on various activities carried out by the Baduy Tribe. The purpose and benefits of this research is to determine the general public's perception and view of the moral value of the implementation of the seba Baduy ceremony of the Sunda Wiwitan indigenous people. The research method used is descriptive qualitative with library research techniques and observation through questionnaires in the form of questionnaires. Data processing is carried out by analyzing theories and research results from articles, books, and other libraries as well as analyzing the results of questionnaires which are then presented in a detailed and comprehensive descriptive manner. The results of the study indicate that the reception and views of the general public on the moral value of the implementation of the seba ceremony are included in the tofu category and are appreciated and appreciated by the surrounding community, in this case the object of research. The series of seba ceremonies are carried out with traditional ceremonies and meetings with government officials at both the regency and provincial levels by providing a number of crops produced by the Baduy Tribe. In addition, the seba ceremony is proof of the existence of traditional recognition and aims to establish a relationship between the Kanakes community and the government. The seba ceremony is part of the Kanakes community's obligation to the Sunda Wiwitan religious belief so that it needs to be preserved in a sustainable manner because it is a pikukuh karuhun that must be maintained.